FORTIFICATION OF SNAKE HEAD FISH (Channa striata) FLOUR ON SEAWEED (Eucheuma cottonii) ICE CREAM TO ACCEPTANCE CONSUMER - Tongam Poriaman Simatupang; Desmelati '; N Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted to determine the effect of fortification ofsnake head fish (Channa striata) on seaweed (Eucheuma cottonii) ice cream tocostumer acceptance. The experimental designed used in this research wasCompletely Randomized Design (CRD), with four treatments ; EK0 (seawead icecream without snake head fish flour), EK1 (seawead ice cream with 5% of snakehead fish flour), EK2 (seawead ice cream with 10% of snake head fish flour) andEK3 (seawead ice cream with 15% of snake head fish flour). The experiment wastriplicated with experiment 12 units. The treatment with 5% of snake head fishflour (EK1) was most preferable by consumer acceptance for apperance 83.75%(67 people), sense 80% (64 people), scent 68.75% (55 people) and texture 63.75%(51 people). The proximate analysis EK1 for moisture content 43.53%, proteincontent 22.69%, fat content 10.22%, emulsion 83.15% and melting time for 12.38minutes.Keywords: Ice cream, Seaweed, snake head flour